Botulinum Toxin for a Better Scar in Cleft Lip Surgery: A Prospective Randomized Control Trial. Issue 1 (January 2022) - Sonane, Jubin; Sharma, Ramesh K.; John, Jerry R.; Sharma, Raman
Abstract : Introduction: An unsightly scar following cleft repair can undo the good work of even an experienced surgeon. A functioning orbicularis oris muscle beneath the lip scar maintains a zone of dynamic tension resulting in a stretched scar. Botulinum toxin type A (BTA) can be used to create a temporary paralysis of the orbicularis muscle during the healing phase. This may lead to better scar formation after a cleft lip repair. Method: The present prospective randomized control trial enrolled 28 infants with unilateral cleft lip undergoing primary lip repair. They were randomized to receive injection of either BTA (botox group) or normal saline (control group) intraoperatively into adjacent orbicularis oris muscle immediately after completion of cleft lip repair. Blinded experts reassessed the scar after 6 months. Objective assessment was undertaken employing Visual Analogue Scale (VAS), Vancouver Scar Scale (VSS), and photographic scar width measurements. Results: Twenty-two subjects were able to complete a follow-up duration of 6 months. Children in the BTA (Botox Group) had a statistically significantly better VAS score and lesser scar width compared to the control group. However, the difference in the VSS score between both groups was not statistically significant. On comparing patients with cleft lip alone with cleft lip and palate, no statistically significant difference was found in VAS, VSS, and scar width. There were no complications associated with the use of botulinum toxin A. Conclusions: Botulinum toxin type A injection is a safe and effective addition to improve scar appearance following cleft lip repair. There was improvement in appearance of the scar in terms of width, but no improvement was seen in the scar pigmentation. The scar outcome is independent of cleft lip classification. Abstract : Supplemental Digital Content is available in the text